Role of “ethical investments” in increasing the level of investment attractiveness of corporations: Russian and foreign experience - A. P. Laktyushina; P. S. Shcherbachenko (Вестник университета)
It is very important to constantly increase investment attractiveness for a company, evaluating and improving it according to various indicators and factors. The following include: financial position of the company, market stability, level of competitiveness, management, structure of liabilities, etc. But it is also important to assess the social role of the company in its impact on society. Recently, the topic of business social responsibility has been widely discussed, and it is not a secret that when evaluating a company from the point of view of a potential object for attracting investments, investors pay close attention to its corporate social responsibility. In this paper, we will talk about the so-called “ethical investments”, which help to improve the reputation and image of the company, thereby increasing its investment attractiveness.